PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS METODE GASING UNTUK PENGUASAAN MATERI GETARAN HARMONIS SISWA KELAS X SMA - Br Bangun, Lonaria; Syahril, Syahril; Ma’aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning tools developed are physics learning tools in the form of Learning Implementation Plan (RPP), Student Worksheet (LKPD) and Material Mastery Test based on Gasing Method. The purpose of this study was to produce Learning Tools on valid Harmonic Vibration materials. This research is expected to be a reference in making reference in making a valid learning device, especially in harmonious vibration material. This type of research is Research and Development (R &D) using 4D Models. This research is only conducted until the development stage. The research instrument used is the Learning Device Instrument validation assessment sheet used by the validator to assess the learning device. Data analysis in this study using descriptive analysis, by calculating the validation score of each indicator of the learning device. The results showed that The Gasing Method-Based Learning Tool was declared valid with an average validation of 3.06 with a high category (T), so that the learning device is declared worthy of use in learning for the mastery of the material of harmonious vibration of class X SMA.Key Words: Learning Tools, Gasing Method, Harmonious Vibration.